Mortgage lending and financial stability in Asia - Peter J. Morgan; Yan Zhang (Asian Development Bank Institute (ADBI), 2015)
We estimated the effect of the share of mortgage lending by individual banks (together with some control variables) on two measures of financial stability - the bank Z-score and the nonperforming loan ratio - for a sample of 212 banks in 19 emerging Asian economies for 2007-2013 from the Bankscope database. We find some evidence that an increased share of mortgage lending is positive for financial stability, specifically by lowering the probability of default by financial institutions and reducing the nonperforming loan ratio, at least in noncrisis periods, for levels of mortgage shares up to 30%-40%. For higher levels of mortgage lending shares, the impact on financial stability turns negative. We also find that the share of mortgage lending can be a useful measure of both financial development and financial inclusion. This finding most likely reflects the effect of a higher share of mortgage lending in diversifying the mix of banks' assets and, thereby, reducing overall risk. However, if the share of mortgage lending is too high, then the diversification effect diminishes. Therefore, the challenge is to balance the expected improvement in financial stability due to asset diversification against negative impacts that might result from easier lending standards or overly rapid increases in mortgage lending that could trigger a bubble in the housing market. This highlights the need for prudent monetary policy and macroprudential policy measures to forestall the development of such bubbles.
Keywords: G21; O16; R3; 330; financial stability; mortgage loan ratio; mortgage lending